2017
DOI: 10.1111/apt.14243
|View full text |Cite
|
Sign up to set email alerts
|

Reduced risk of decompensation and death associated with use of statins in patients with alcoholic cirrhosis. A nationwide case‐cohort study

Abstract: Our results showed an association between regular use of statins and reduced mortality in patients with alcoholic cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…Similarly, there was no statistically significant increase in mild (diarrhea, myalgia) to severe (ascites, spontaneous bacterial peritonitis, and variceal hemorrhage) adverse events. In five retrospective studies with cohort sizes of 343 to 40,512, no increase in adverse events or mortality was noted . Meta‐analysis shows that rather than worsening of liver function, there was a statistically significant improvement in disease progression and mortality …”
Section: Statins Largely Remain Safe In Compensated Cirrhosismentioning
confidence: 95%
See 1 more Smart Citation
“…Similarly, there was no statistically significant increase in mild (diarrhea, myalgia) to severe (ascites, spontaneous bacterial peritonitis, and variceal hemorrhage) adverse events. In five retrospective studies with cohort sizes of 343 to 40,512, no increase in adverse events or mortality was noted . Meta‐analysis shows that rather than worsening of liver function, there was a statistically significant improvement in disease progression and mortality …”
Section: Statins Largely Remain Safe In Compensated Cirrhosismentioning
confidence: 95%
“…In five retrospective studies with cohort sizes of 343 to 40,512, no increase in adverse events or mortality was noted. [29][30][31][32][33] Meta-analysis shows that rather than…”
Section: Statins Largely Remain Safe In Compensated Cirrhosismentioning
confidence: 99%
“…(2) It has been shown that results can be biased toward a protective effect of treatment by either misclassified immortal time or excluded immortal time. (3) They also did not report the mean interval between the date of diagnosis of cirrhosis and the date of first statin prescription, which would influence the magnitude of bias.…”
Section: To the Editormentioning
confidence: 99%
“…Actually, besides the two studies (including the current one) showing beneficial effects of statin in reducing decompensation rate among hepatitis Band hepatitis C-related cirrhosis, (1,2) a recent population study also revealed similar beneficial effects of statin in patients with alcoholic cirrhosis. (3) Furthermore, a recent prospective study showed that adding simvastatin to standard therapy was associated with a survival benefit for patients with Child-Pugh class A or B cirrhosis. (4) Nevertheless, we agreed that there may exist unmeasured confounders that would impact on our results.…”
Section: Replymentioning
confidence: 99%
“…The study by Bang et al is a large‐scale observational study that examines the effect of statin use on decompensation and mortality in alcohol‐related cirrhosis, and uses a number of techniques to minimise both adherer and time‐related bias. The authors analysed Danish national data registries retrospectively from 1995 to 2014 and identified an impressive 19 105 patients with alcoholic cirrhosis.…”
mentioning
confidence: 99%